Le statut de la sainteté dans les « religions politiques » - Yves Bizeul (Conserveries Mémorielles)
“Political religions” transform holiness into self-sacrifice in the name of political action. Furthermore, the saint hereby becomes a hero (of work, of war, or of propaganda) and an armed or unarmed missionary serving a holy “cause”. He does not seek to withdraw from the visible world even if he mundanely practices an ascetic lifestyle. On the contrary, he wants to transform the world by his commitment. The new secular holiness is not about contemplation but about action and creatio ex nihilo. It has, therefore, a quasi-divine character. The party and its charismatic leader, who are seen as incorporations of the whole body politic, take the empty place God has left. The secular saint is a potential martyr inasmuch as he has a providential and Promethean mission to fulfil. Because of this, he often becomes the centre of a devotional cult after his death.